2021
DOI: 10.3390/polym13224014
|View full text |Cite
|
Sign up to set email alerts
|

Processing, Performance Properties, and Storage Stability of Ground Tire Rubber Modified by Dicumyl Peroxide and Ethylene-Vinyl Acetate Copolymers

Abstract: In this paper, ground tire rubber was modified with dicumyl peroxide and a variable content (in the range of 0–15 phr) of ethylene-vinyl acetate copolymers characterized by different vinyl acetate contents (in the range of 18–39 wt.%). Modification of ground tire rubber was performed via an auto-thermal extrusion process in which heat was generated during internal shearing of the material inside the extruder barrel. The processing, performance properties, and storage stability of modified reclaimed ground tire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 55 publications
3
17
0
Order By: Relevance
“…This, in turn, results in the release of decomposition by-products into the atmosphere during subsequent heating. It is worth mentioning that the TVOCs determined by Wiśniewska et al [ 67 ] using the same Micro-Chamber/Thermal Extractor TM system for uncured modified GTR is around 17.8–29.2 µg/g while the processing temperature was set at 130 °C. These values are higher than those achieved in this work (2.8–5.9 µg/g) for modified reclaimed rubber processed at 60 °C.…”
Section: Resultsmentioning
confidence: 99%
“…This, in turn, results in the release of decomposition by-products into the atmosphere during subsequent heating. It is worth mentioning that the TVOCs determined by Wiśniewska et al [ 67 ] using the same Micro-Chamber/Thermal Extractor TM system for uncured modified GTR is around 17.8–29.2 µg/g while the processing temperature was set at 130 °C. These values are higher than those achieved in this work (2.8–5.9 µg/g) for modified reclaimed rubber processed at 60 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The authors indicated that it is necessary to keep the devulcanization temperature as low as possible for the efficient devulcanization of tire rubbers. Figure 4 presents the infrared camera images for modified GTR, which confirms that the kind of used modifier might have a significant impact on the temperature of materials, especially when the process is performed in auto-thermal conditions [255].…”
Section: Low-temperature Devulcanization and Modification Of Gtrmentioning
confidence: 70%
“…The authors indicated that it is necessary to keep the devulcanization temperature as low as possible for the efficient devulcanization of tire rubbers. Figure 4 presents the infrared camera images for modified GTR, which confirms that the kind of used modifier might have a significant impact on the temperature of materials, especially when the process is performed in auto-thermal conditions [255]. The infrared camera images for modified ground tire rubber (GTR) samples: GTRDCP; GTRDCP + 5 phr EVA; GTRDCP + 10 phr EVA; GTRDCP + 15 phr EVA (DCP-dicumyl peroxide, EVA copolymer with 18% vinyl acetate) (adopted from [255]).…”
Section: Low-temperature Devulcanization and Modification Of Gtrmentioning
confidence: 73%
See 1 more Smart Citation
“…Alternatively, ELTs may find utilization at erosion control; mine stabilization; in the production of asphalt; filler in cement composites by using rubber crumb produced by tire crushing; or alternatively reclaiming and devulcanization [ 6 , 7 , 8 ]. In this regard, ELTs have attracted significant attention of several research teams considering its beneficial properties such as endurance, thermal stability, chemical resistance, and mechanical parameters [ 9 ].…”
Section: Introductionmentioning
confidence: 99%